ARTIFICIAL INTELLIGENCE AND PSYCHOLOGICAL – PROPAGANDA OPERATIONS IN THE CONTEXT OF THREAT TO NATIONAL SECURITY - Proroković, Dušan; Parezanović, Marko (The Policy of National Security, 2023)
The key characteristic of international relations is their anarchy and in modern conditions this is manifested by the continuous performance of psychological-propaganda operations (PsyOp) by some actors against others. PsyOp represent the first stage in the preparation and implementation of a hybrid war, but they can also be an end in themselves. Over time, they have become an indispensable means of ensuring national security. National security is ensured by eliminating or relativizing the conflicting interests of rivals (enemies) against whom PsyOp are directed. A new moment in the application of this concept is the development and (mis)use of artificial intelligence (AI). The capacities of artificial intelligence for designing and implementing PsyOp far exceed human potential. It can introduce international relations into a stage of constant and permanent conflicts by carrying out continuous psychological-propaganda operations and starting hybrid wars that will never end. Another danger lies in the claim of the creators of AI that the AI has its own logic, and because of this, in the future, it will depend less and less on given inputs. In an anarchic environment, AI can independently induce and generate wars by conducting unpredictable PsyOp. The author's conclusion is that the combination of traditional anarchy and new technology worsens the national security of states, but indirectly also global security, and therefore it is necessary to think about different ways of limiting the use of AI in international relations.
Keywords: artificial intelligence; hybrid war; psychological-propaganda operations; national security; international relations; anarchy